A novel process on friction aided deep drawing using tapered blank holder divided into four segments - Hassan, M.A.; Suenaga, R.; Takakura, N.; Yamaguchi, K. (2005)
A new technique on friction aided deep drawing has been proposed. A metal blank holder was designed to be of two layers: stationary layer or base with four planes of 5degrees taper angle and moving layer divided into four tapered segments. Under appropriate blank holding force, these four segments can move radially to the die opening with a constant speed by using a specially designed compression tool. The main function of this developed blank holding device is adopting the frictional force between the blank and the blank holder to work in the useful drawing direction likewise the function of the rubber ring used in Maslennikov's process. Drawing deformation is efficiently performed by using an assistant metal punch, which is supplemented with a hydraulic cylinder to provide a constant punch force during the drawing process. The drawing mechanism and the effects of drawing conditions are mainly investigated to characterize the merits and defects of the proposed process. Since successful deep cups of drawing ratio 3.76 have been produced the possibility of the present technique is already confirmed, however, further investigations are needed to enhance the drawing efficiency. (C) 2004 Elsevier B.V. All rights reserved.